Metadata-driven software systems in biomedicine designing systems that can adapt to changing knowledge - Nadkarni, Prakash M. (Health informatics., 2011)
To build good systems, one needs both good development skills as well as a thorough knowledge of the problem one is trying to solve. Knowledge of software history--what has worked and what hasn't--also helps in these types of detailed projects. Metadata-Driven Software Systems in Biomedicine lays down some of the foundations and provides a knowledge-base to assist this process. The technical portion of the book consists of database schemas and working code that provide non-trivial examples for the practitioner who is conversant with software development and wishes to employ the approaches described in the book.  Eight of the ten chapters include case studies, while the book also includes extensible designs in biomedical applications: electronic medical records, clinical study data management systems, laboratory research support systems, ontologies, and production-rule subsystems. This book is therefore ideal for individuals who have to interact with large biomedical database systems in an information-technology or informatician capacity, build interfaces to such systems or design new systems themselves.